Cover Feature: Computational Design and Study of Artificial Selenoenzyme with Controllable Activity Based on an Allosteric Protein Scaffold (Chem. Eur. J. 44/2019). Issue 44 (11th June 2019) - Li, Siyuan; Xu, Wanjia; Chu, Shengnan; Ma, Ningning; Liu, Shengda; Li, Xiumei; Wang, Tingting; Jiang, Xiaojia; Li, Fei; Li, Yijia; Zhang, Dongmei; Luo, Quan; et al.
Abstract : A computational protocol that combines docking, molecular dynamics, and MM‐PBSA was described to guide the design of an artificial selenoenzyme based on a Ca 2+ ‐responsive recoverin (Rn) protein. The catalytically active site of glutathione peroxidase (GPx) can be precisely incorporated into the allosteric domain of Rn, leading to a high GPx activity and tightly controlled function for the catalyzed reduction of H2 O2 by glutathione (GSH). These results provide important insights into how to create an enzyme‐like site in non‐homologous protein scaffolds. More information can be found in the Full Paper by Q. Luo et al. on page 10350 .